Bibliometric analysis of antibacterial activity of Centella asiatica: A study based on Scopus database - Asti Arum Sari, Rima Munawaroh, Eko Naning Sofyanita (Journal of Applied Pharmaceutical Science, 2023)
Centella asiatica (L.) Urb. has been recognized as a brain tonic. Other effects of C. asiatica have been widely investigated and reported, such as its antibacterial effect. However, there is no bibliometric study on this topic. Therefore, we performed bibliometric analysis to examine the papers related to the study of C. asiatica as an antibacterial agent. Bibliographic information of pertinent studies was collected from Scopus database. In this study, 89 papers published between 1997 and 2022 were selected. Bibliometric analysis was performed using Visualization of Similarities viewer (VOSviewer) version 1.6.18. Having been analyzed, it was found that Ubon Ratchathani University from Thailand was the most productive affiliation and the Journal of Ethnopharmacology was the most productive journal on the topic of antibacterial activity of C. asiatica. India was the most productive and the most collaborating country. According to the study of the most influential papers, author-based bibliographical coupling network, as well as keyword co-occurrence network and overlay, the variants of selected papers were from solvent extraction, bacteria-tested, plant components, and product formulations. We also found out that, following the formulation approach, both in vivo preclinical and clinical trials on this topic remain a potential study to be investigated to embrace phytomedicine as a therapeutic option.
Keywords: Centella asiatica, antibacterial, bibliometric, Scopus, VOSviewer